2019
DOI: 10.1088/1361-6463/ab1e2a
|View full text |Cite
|
Sign up to set email alerts
|

Broadband RCS reduction for electrically-large open-ended cavity using random coding metasurfaces

Abstract: A scattered radar signal by an electrically-large open-ended cavity involves information of the target. Therefore, controlling the Radar cross section (RCS) of the cavity is significant for target stealth. Coding metasurfaces have promised great possibilities for full control of the electromagnetic waves, especially for reducing RCS by random coding metasurfaces. Here, we report an approach to realize broadband RCS reduction of electrically-large openended cavities through loading random coding metasurfaces on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…As shown in Figure 1e, all the thin films show high transparency in the wavelength of visible light visible (250–800 nm). Figure 1f shows the energy band gap ( E g ) value calculated by the optical transmittance versus wavelength [Equation ()] [ 18 ] αhν = AhνEg1/2 where α is the optical absorption coefficient, h is Plank's constant, and v is frequency of light, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1e, all the thin films show high transparency in the wavelength of visible light visible (250–800 nm). Figure 1f shows the energy band gap ( E g ) value calculated by the optical transmittance versus wavelength [Equation ()] [ 18 ] αhν = AhνEg1/2 where α is the optical absorption coefficient, h is Plank's constant, and v is frequency of light, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that with the Li doing content increasing, the transfer curve shifts toward the negative voltage direction. The mobility (μ) and subthreshold swing ( SS ) are calculated from the following equation [ 20 ] ID=WμCi[(VGVTH)2]2L SS =dfalse(log10IDfalse)dfalse(VGfalse)1 where W is channel width, L is the channel length, and C i is the specific capacitance of the AlLiO film at 20 Hz (about 450 nF cm −2 ). The electrical performances are calculated and summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…shape, edge, and surface of an object to minimize reflections back to the radar, is one of the scattering methods [3]. Nonabsorptive metasurfaces (MSs) offer another approach by eliminating scattering between elements through equivalent amplitude and out-of-phase scattered waves [4][5][6][7][8]. On the other hand, radar absorbing materials are employed to absorb electromagnetic (EM) energy and convert it into heat, thereby reducing the RCS.…”
Section: Introductionmentioning
confidence: 99%
“…Different from absorbing metamaterials based on amplitude regulation, coding metamaterials, which are based on phase regulation, can redirect scattered energy into nonmirror direction, hence suppressing the strong specular reflection [14]. Since magnetic materials are not required, the reflection reduction metasurface is promising for the application in high temperature environment [15]. An all-dielectric heat-resisting metasurface composed of patterned aluminum nitride ceramics has been designed to achieve specular reflection reduction, which cannot meet the mechanical requirements in practice [16].…”
Section: Introductionmentioning
confidence: 99%